Deploying ASP.NET Core Applications: From Fundamentals to Advanced Deployment Strategies. - Trupja, Ervis (linkedin.com, 2024)
Find out how to deploy to on-premises, Azure, and AWS. Go over CI/CD, Docker, Kubernetes, and more. Learn to deploy apps efficiently across environments.